1997
DOI: 10.1165/ajrcmb.17.4.2714
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 and Other Sialoglycoconjugates Inhibit Adenovirus-mediated Gene Transfer to Epithelial Cells

Abstract: Recombinant adenoviruses are currently being evaluated as gene transfer vectors for the treatment of airway diseases. Recent evidence indicates that gene transfer to differentiated airway epithelial cells is inefficient. We hypothesized that apical membrane glycoconjugates, such as the transmembrane mucin MUC1, reduce the efficiency of adenovirus-mediated gene transfer. To address this, studies were performed in primary bronchial epithelial and Madin Darby canine kidney (MDCK) cells transduced to express human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 46 publications
5
57
0
Order By: Relevance
“…This phenomenon was not observed in any of our in vitro studies where vector and protamine could be added simultaneously with good effect. Arcasoy et al 35 reported similar observations when using various polycations in vitro and in vivo. In contrast, Kaplan et al 36 demonstrated that ex vivo preparations of Ad/polycation complexes were effective in augmenting gene transfer of LacZ in mouse lung in vivo.…”
Section: Figure 6 Effect Of Protamine On Ad-mediated Suicide Gene Thementioning
confidence: 58%
See 2 more Smart Citations
“…This phenomenon was not observed in any of our in vitro studies where vector and protamine could be added simultaneously with good effect. Arcasoy et al 35 reported similar observations when using various polycations in vitro and in vivo. In contrast, Kaplan et al 36 demonstrated that ex vivo preparations of Ad/polycation complexes were effective in augmenting gene transfer of LacZ in mouse lung in vivo.…”
Section: Figure 6 Effect Of Protamine On Ad-mediated Suicide Gene Thementioning
confidence: 58%
“…31 In addition to these two receptors, the interaction of charges on the surface of the cell membrane appears to play a significant role in cell binding and entry of adenovirus. Arcasoy et al 35 have shown that Ad-mediated transducibility of epithelial cells is increased when the negatively charged sialic acid residue are removed from the epithelial cell membranes. The fiber receptor mediated pathway is not involved in the increased gene transfer observed with the use of polycations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 This may be relevant because related molecules such as MUC1 and other sialylated glycoconjugates have been shown to decrease adenovirus-mediated gene transfer, possibly by interfering with viral attachment or internalization. 43 In the future, better understanding of the mechanisms by which this inflammation interferes with adenovirusmediated gene transfer may lead to more specific approaches to enhancing gene transfer in CF patients with inflamed airways.…”
Section: Discussionmentioning
confidence: 99%
“…As many microbial pathogens are known to trigger shedding of the MUC1 extracellular domain (ED) after binding, [24][25][26][27] we tested whether this phenomenon could also be caused by IAV. Supernatants were collected from PR8-infected CHO-K1 control and MUC1 þ cell cultures and the amount of MUC1-ED present in the supernatant was determined by ELISA.…”
Section: Iav Binds To Muc1 and Triggers Shedding Of The Mucin Extracementioning
confidence: 99%